1983
DOI: 10.1021/ja00347a085
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and emission characteristics of merocyanine 540 in microemulsions

Abstract: Cyanine dyes are heterocyclic chromophores that are extensively used in a number of areas. For example, they are used as photographic sensitizers, in photographic filter layers, for textiles, and in chemotherapy.1 Recently they have also been examined as Registry No. Merocyanine 540, 62796-23-0; sodium cetyl sulfate, 1120-01-0; cetyltrimethylammonium bromide, 57-09-0; sodium dodecyl sulfate, 151-21-3. gem -Alkylcyclopentadienes. 2. Secondary Deuterium Kinetic Isotope Effect Study of the Cycloaddition of Diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…It is a solvatochromic dye whose absorption spectrum shifts with polarity [34,35,37]. As many amphipathic molecules, it has a strong tendency to dimerize in aqueous solutions [26]. The absorption spectrum of the dye in water has a double-banded structure (501 and 533 nm) and the extinction coefficient is concentration dependent, indicating dimerization of the dye [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is a solvatochromic dye whose absorption spectrum shifts with polarity [34,35,37]. As many amphipathic molecules, it has a strong tendency to dimerize in aqueous solutions [26]. The absorption spectrum of the dye in water has a double-banded structure (501 and 533 nm) and the extinction coefficient is concentration dependent, indicating dimerization of the dye [38].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported for MC540 in alcoholic media (Hoebeke et al, 1988;Aramendia et al, 1988), the shape of the absorption spectrum of the photoisomer is similar to that of the thermodynamically stable ground state although the absorbance is somewhat lower. The presence of two absorption maxima (490 and 530 nm) is likely to be the consequence of dye aggregation as in the case of the ground state (Dixit and Mackay, 1983). The analysis of the photoisomer decay revealed that at least two exponentials with close lifetimes are involved and that the major contribution arose from the faster one.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, little is known about MC540 photophysics in water. The only report is that of Dixit and Mackay (1983) where it is shown that MC540 molecules may form aggregates and may emit fluorescence. The present work is devoted to the investigation of 3MC540 in water: surprisingly, the triplet yield was found to be excitation wavelength dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence of the supernatant, representing MC540 released from the cells, was subtracted from the fluorescence of the cell suspension to obtain fluorescence data of cellbound MC540. The relative fluorescence quantum yield is defined as the quantum yield of bound MC540 divided by the quantum yield of the dye at the same concentration in aqueous solution, both measured at the emission maximum [19]. Lipid peroxidation was assayed by measuring the generation of thiobarbituric acid reactive species (TBARS) as described by Miller et al [20].…”
Section: Methodsmentioning
confidence: 99%